The Current Role of Staging Laparoscopy in Oesophagogastric Cancer - Convie, L (Ann R Coll Surg Engl, 2015)
INTRODUCTION: Oesophagogastric cancers are known to spread rapidly to locoregional lymph nodes and by transcoelomic spread to the peritoneal cavity. Staging laparoscopy combined with peritoneal cytology can detect advanced disease that may not be apparent on other staging investigations. The aim of this study was to determine the current value of staging laparoscopy and peritoneal cytology in light of the ubiquitous use of computed tomography in all oesophagogastric cancers and the addition of positron emission tomography in oesophageal cancer. METHODS: All patients undergoing staging laparoscopy for distal oesophageal or gastric cancer between March 2007 and August 2013 were identified from a prospectively maintained database. Demographic details, preoperative staging, staging laparoscopy findings, cytology and histopathology results were analysed. RESULTS: A total of 317 patients were identified: 159 (50.1%) had gastric adenocarcinoma, 136 (43.0%) oesophageal adenocarcinoma and 22 (6.9%) oesophageal squamous carcinoma. Staging laparoscopy revealed macroscopic metastases in 36 patients (22.6%) with gastric adenocarcinoma and 16 patients (11.8%) with oesophageal adenocarcinoma. Positive peritoneal cytology in the absence of macroscopic peritoneal metastases was identified in a further five patients with gastric adenocarcinoma and six patients with oesophageal adenocarcinoma. There was no significant difference in survival between patients with macroscopic peritoneal disease and those with positive peritoneal cytology (p=0.219). CONCLUSIONS: Staging laparoscopy and peritoneal cytology should be performed routinely in the staging of distal oesophageal and gastric cancers where other investigations indicate resectability. Currently, in our opinion, patients with positive peritoneal cytology should not be treated with curative intent.